2021
DOI: 10.1186/s13287-020-02079-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: RNA-seq reveals tight junction-relevant erythropoietic fate induced by OCT4 in human hair follicle mesenchymal stem cells

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Intercellular junctions, such as adherens and tight junctions, are responsible for connecting each cell to each other to establish a tight skin barrier 43 . A recent study showed that overexpression of Oct4 influenced the morphology and adhesion of human hair follicle mesenchymal stem cells 65 . We found that loss of Oct4 in skin keratinocytes diminished E-cadherin and β-catenin from cell-cell contacts by altering their localization, and inhibited their colocalization at the plasma membrane, possibly by impairing the interaction between the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular junctions, such as adherens and tight junctions, are responsible for connecting each cell to each other to establish a tight skin barrier 43 . A recent study showed that overexpression of Oct4 influenced the morphology and adhesion of human hair follicle mesenchymal stem cells 65 . We found that loss of Oct4 in skin keratinocytes diminished E-cadherin and β-catenin from cell-cell contacts by altering their localization, and inhibited their colocalization at the plasma membrane, possibly by impairing the interaction between the two proteins.…”
Section: Discussionmentioning
confidence: 99%